Evaluating historical changes in a mussel bed community in northern California - Emily K. Longman; Sarah Merolla; Stefan A. Talke; Nicholas Trautman; John L. Largier; Leslie Harris; Eric Sanford (Scientific Reports)
Abstract Marine foundation species are increasingly impacted by anthropogenic stressors, driving a loss of diversity within these critical habitats. Prior studies suggest that species diversity within mussel beds has declined precipitously in southern California, USA, but it is unclear whether a similar loss has occurred farther north. Here, we resurvey a mussel bed community in northern California first sampled in 1941 to evaluate changes in diversity after 78 years. More broadly, we explore the value and potential challenges of using imperfect historical data to assess community changes. Our 2019 survey documented 90 species/taxa across 10 phyla. The majority of species (~ 72%) were common to all replicate plots, suggesting that variation in species diversity over small spatial scales was unlikely to mask temporal changes. In contrast to results from southern California, we observed no decline in species diversity between timepoints. However, there were shifts in species composition, with an increase in the abundance of southern species and a decrease in northern species, consistent with warming observed at a nearby shoreline site. Overall, our findings are an encouraging sign for the health of this mussel bed community in northern California and illustrate how non-traditional data can contribute to assessments of long-term ecological change.